UPAYA HUKUM KREDITOR SEBAGAI PENANGKAL RISIKO HAPUSNYA HAK ATAS TANAH YANG DIAGUNKAN - Ghansam Anand (JURNAL AKTA YUDISIA, 2020)
ABSTRACT             The creditor certainly wants a position that is not the same as other creditors, because the same position with other creditors means getting equal rights with other creditors of the proceeds from the sale of the debtor's property, if the debtor is liable to the promise. The balanced position does not provide certainty of guaranteed return of receivables. The more creditors of the debtor are concerned, the less likely it is to guarantee the return of the receivable if for some reason the debtor becomes insolvent (unable to pay its debts). The procurement of legally guaranteed copyrights is to provide a position for a particular creditor to take precedence over other creditors. It is also the objective of the existence of Mortgage Rights as regulated by Law Number 4 Year 1996 concerning the Right of Million of Land and Land Related. One of the events that eliminated the Mortgage right is mentioned in Article 18 paragraph (1d) UUHT, that as the last mentioned basis for the abolition of Mortgage right is the abolition of land rights. The abolition of land rights takes place over time, for which the right is granted. Rights that are lower in rank than property rights such as the right to use, the right to use and the right to use are limited in time, even if physically still exist. With the termination of the rights to the land concerned, the rights to the land concerned shall return to the concerned owner or owner and if such right is granted by the state, then the land is returned to the state power. Thus, the creditor of the dependent will lose his position as the preferred creditor. Keywords: Creditors, Debtors, Deposit Rights